Towards economic stability: Analysis of Msme business sustainability in central Java province post the COVID-19 pandemic - Aziz, Fathul Aminudin; Utami, Hastin Tri; Wanojaleni, Kartika; Edy, Slamet Cahyo (Edelweiss Applied Science and Technology, 2024)
The primary objective of this study is to determine, via empirical testing, which internal and external factors have the greatest impact on micro, small, and medium-sized enterprises (MSMEs). (b) Conduct an empirical study to determine are affected by external factors that influence their sustainability. c) Find out how much MSMEs really use information and digital technologies by conducting an empirical test. (d) To see how well businesses were able to keep running following the COVID-19 pandemic. The crux of the matter is to understand how the pandemic has affected MSMEs from the inside and out, including how income has dropped, how consumer behavior has changed, and how supply chains have changed, acknowledging the merits and demerits, adjusting business models to account for human resources availability, fostering collaboration and partnerships, enabling digital empowerment, regulating policies, and providing education and training. The analysis’s findings can inform policy suggestions and strategy formulation to help micro, small, and MSMEs in Central Java Province weather the post-COVID-19 economic storm.